Synergistic use of peat and charred material in growing media – an option to reduce the pressure on peatlands?. Issue 2 (3rd April 2017) - Kern, Jürgen; Tammeorg, Priit; Shanskiy, Merrit; Sakrabani, Ruben; Knicker, Heike; Kammann, Claudia; Tuhkanen, Eeva-Maria; Smidt, Geerd; Prasad, Munoo; Tiilikkala, Kari; Sohi, Saran; Gascó, Gabriel; et al.
Abstract: Peat is used as a high quality substrate for growing media in horticulture. However, unsustainable peat extraction damages peatland ecosystems, which disappeared to a large extent in Central and South Europe. Furthermore, disturbed peatlands are becoming a source of greenhouse gases due to drainage and excavation. This study is the result of a workshop within the EU COST Action TD1107 ( Biochar as option for sustainable resource management), held in Tartu (Estonia) in 2015. The view of stakeholders were consulted on new biochar-based growing media and to what extent peat may be replaced in growing media by new compounds like carbonaceous materials from thermochemical conversion. First positive results from laboratory and greenhouse experiments have been reported with biochar content in growing media ranging up to 50%. Various companies have already started to use biochar as an additive in their growing media formulations. Biochar might play a more important role in replacing peat in growing media, when biochar is available, meets the quality requirements, and their use is economically feasible.